Pemberdayaan Ibu-Ibu PKK Desa Parit Baru Melalui Pelatihan Pembuatan Lilin Aromaterapi Berbasis Limbah Minyak Jelantah - Xavier, Albertus Arjuna Langgeng; Azazi , Anwar; Aprilliani, Novi Krisentia; Nafisah, Tengku Savira; Kristiani, Amanda Putri (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
Used cooking oil is a common type of household waste that is often disposed of carelessly and can harm the environment. Parit Baru Village, with its dense population, produces a large amounts of used cooking oil waste. Meanwhile, the role of PKK (Family Welfare Movement) as change agents in the community has not been fully utilized in managing such waste. Therefore, this program aims to empower PKK through training in making aromatherapy candles from used cooking oil waste, as a means to raise environmental awareness and create opportunities for creative economic activities. Using a Participatory Learning and Action (PLA) approach, this program involving technical training, discussions, and hands-on practice in processing used cooking oil into aromatherapy candles. Through this program, they become more aware of the dangers of throwing away used cooking oil carelessly and gain new skills in making aromatherapy candles from used cooking oil waste. The resulting products have economic potential and can help reduce household waste. Thus, this activity not only provides education but also opens up new business opportunities based on the creative economy, which is expected to encourage the creation of independent household-scale businesses that contribute to family welfare and environmental conservation.